Influence Of Plastifying Additives On The Properties Of Cement Stone - Shakirov Tuygun Turgunjonovich; Muminova Nilufar Abdulla Kizi (International Journal on Orange Technologies, 2021)
The article presents the results of research work on the development of the properties of binders with chemical additives and determines the optimal compositions. Today, along with water, filler and binder, additives have become an indispensable component of the concrete mix. Among the many types of chemical additives, plasticizers occupy a separate place, especially the most effective of them are superplasticizers. The most important physical and mechanical characteristics of cement with chemical additives are discussed below